Goods traffic centres in Germany: The rise or fall of a multi-modal transport infrastructure? - Kinder, Sebastian (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
Since the early 1990s there has been intensive discussion in Germany on the construction of goods-traffic centres. Today more than 40 projects have reached an advanced stage of planning or of realisation. Originally the idea of goods-traffic centres reflected aims emanating from the fields of transportation, economic, urban-development as well as environmental policy. Early practical experience of goods-traffic centres has led to the economic aims behind these centres being emphasised at the expense of the other aims. There is a future for goods-traffic centres if they are developed consistently as centres of logistic competence in the regions in which they are located.